The future of the Malaysian older employees: an exploratory study - Chan, Benjamin Yin Fah; Paim, Laily; Masud, Jariah; Tengku Abdul Hamid, Tengku Aizan (Canadian Center of Science and Education, 2010)
Malaysia older workers might choose either to continue working or stop working upon retirement due to various working accessibility barriers. This paper examined the factor/s that drives them continue working or stop working. Besides, this paper also focused on the respondents’ saving in their provident fund and exploring how the respondents utilized their provident fund in old age. This paper provides information on employment issues and financial aspects among the older workers as well as some recommendations in improving the employability and financial security among Malaysian elderly.